Critical Success Factor of Demand Towards New Product of Islamic Home Financing: A Pilot Test - Liza Ghazali, Puspa; Ansyari Guci, Dede; Arni Syed Jaaffar, Sharifah; Simbolon, Ramadona; Elviani, Sri; Abas, Sayid; Ekalestari, Susi; ., Fajrillah; Hazimi Mohammed Foziah, Nik; Mamat, Mustafa (International Journal of Engineering and Technology, 2018)
This research focuses on the new product of home financing in Malaysia. The purpose of the research is to examine if there is any relationship between knowledge, benefit, marketing and quality towards new constructed product of home financing. A hundred respondents of people who have home financing have been chosen in the field of research in Kuala Terengganu and Kuala Nerus, Malaysia. The method of instrument was using questionnaires and made up of five variables. Reliability analysis was the statistic for found the result. There were six variables got high Cronbachâ€™s-alpha, which was greater than 0.6 means accepted. It can be concluded that the suitability test of the instruments which was adapted from previous study to the population and situation of the research was accepted. Yet, by using Kolmogrov Smirnov test, it was found that the entire variables were distributed normally. Researcher concluded that the analyze data by using parametric technique analysis.Â Â